2013
DOI: 10.1124/dmd.113.051623
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen–Activated Protein Kinase Regulates Nuclear Receptor CAR that Activates the CYP2B6 Gene

Abstract: The constitutive active/androstane receptor (CAR) regulates hepatic drug metabolism by activating genes, such as cytochrome P450, and certain transferases. p38 Mitogen-activated protein kinase (MAPK) is highly activated in human primary hepatocytes but barely in human hepatoma cell lines including HepG2 cells. Liganded-CAR induced CYP2B6 mRNA in human primary hepatocytes far more effectively than in HepG2 cells ectopically expressing CAR. In the present study, we found that activation of p38 MAPK by anisomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
2
11
1
Order By: Relevance
“…1A). The results of a previous experiment with small-interfering RNA confirmed that this synergy was, in fact, mediated by p38 MAPK (Saito et al, 2013b). Upon activation, CAR binds the DNA sequence called PBREM within the CYP2B6 promoter to activate it.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…1A). The results of a previous experiment with small-interfering RNA confirmed that this synergy was, in fact, mediated by p38 MAPK (Saito et al, 2013b). Upon activation, CAR binds the DNA sequence called PBREM within the CYP2B6 promoter to activate it.…”
Section: Resultssupporting
confidence: 64%
“…In liver cells, phosphorylated p38 MAPK is accumulated in the nucleus to activate various transcription factors and protein kinases. We have recently demonstrated that p38 MAPK is essential for CAR to activate the cytochrome P450 2B6 (CYP2B6) gene in human hepatoma HepG2-derived cells (Saito et al, 2013b). In the present study, we revealed that p38 MAPK forms a complex with CAR to promote the CAR-mediated transcription in the nucleus.…”
Section: Introductionsupporting
confidence: 48%
“…CAR requires p38 MAPK activity to activate the CYP2B6 gene in HepG2 cells (Saito et al, 2013). Our recent study with mouse CARexpressing HepG2 cells and mouse primary hepatocytes demonstrated that, in the nucleus, p38 MAPK recruits CAR to the PBREM of the CYP2B promoter for activation and subsequently phosphorylates threonine 38 for inactivation (Hori et al, 2016).…”
Section: Negishimentioning
confidence: 99%
“…lytic subunits, PPP1R16A, interacts with CAR at the cell membrane and prevents nuclear translocation of CAR, which is dependent on phosphatase activity [22] . Moreover, the mitogenactivated protein kinase (MAPK) p38 also regulates human CAR activity on the CYP2B6 gene [23] . This additional evidence adds further complexity to the phosphorylation-dependent nuclear translocation of CAR.…”
Section: Nuclear Translocation Of Carmentioning
confidence: 99%